Pengaruh Persepsi Harga, Persepsi Kualitas Produk, dan Gaya Hidup Konsumen Terhadap Keputusan Pembelian Menu Signature McDonald’s Banjarmasin - Nurul Ismi; Maryono (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
The growth of the culinary business, especially fast food restaurants, has increased rapidly due to the increasing of people’s mobility and busy activities. Fast food restaurants are believed to be able to meet the consumption needs of people who have limited time because of their busy lifestyle. McDonald's restaurant is one of the fast food restaurants that has opened a branch in Banjarmasin to attract the interest and attention of many people. The objective of this study is to indentify the influence of perceived price, perceived product quality and consumer’s lifestyle of Purchase Decisions of McDonald’s Banjarmasin signature menu. This study used a sample of 115 respondents with the characteristics of having purchased the McDonald's Banjarmasin signature menu, minimum age of 17 years, and currently living in Banjarmasin City. This research finds that perceived price, perceived product quality and consumer’s lifestyle significantly affect purchase decision. The t test result shows that perceived price (), perceived product quality () and consumer’s lifestyle () partially have significant effect on purchase decision. The coefficient of determination (adjusted R squared) is 0,408, indicating that 40,8% of the purchase decision is influenced by its independent variables